Submaxillary salivary lithiasis - Lanza Barbieri, Mario (Cirugía del Uruguay, 1977)
A 72-year-old patient presented an interesting case of lithiasis in the left submaxi!lar gland. After suffering a classical case of salivary colic with gland tumefaction, there was spontaneous expulsion of three ptyaliths, one of which was over 2 cms, the other two being smaller. The patient was cured in a manner which is not usual and has subsequently been well. Ten days later, clinical and radiological studies showed no signs of lesion and the patient was totally free of symptoms.